Treatment adherence amongst drug users attending public and private methadone maintenance clinics in a northern province of Vietnam - Tuan Anh Le; Giang Hai Ha; Mai Quynh Thi Le; Lien My Hoang Tran; Duyen Thanh Thi Pham; Ninh Hai Thi Tran; Giang Thu Vu; Long Hoang Nguyen; Hai Quang Pham; Cuong Tat Nguyen; Tung Hoang Tran; Kiet Tuan Huy Pham; et al. (BMC, 2020)
Abstract Background Methadone maintenance treatment (MMT) has been proven to be effective in improving health status and the quality of life of illicit drug users. Due to the quick expand of methadone program, socialization through co-payment service is a critical to the success of it. In Nam Dinh, Vietnam, MMT has been used in public clinics and one private clinic. Such effectiveness of this treatment has been found to depend largely on adherence to treatment. This study aims to explore the compliance rate and its influencing factors among drug users between public and private clinics in Nam Dinh province, Vietnam. Methods A cross-sectional study was conducted on 395 participants from January to September in 2018 in three MMT clinics in Nam Dinh, Vietnam. We applied the convenience sampling technique to recruit respondents. Data on socioeconomics characteristics, MMT adherence (measured by Visual Analogue Scale - VAS) and level of social/family support were collected. Results 43.3% of participants reported complete adherence to the MMT program during the time of research. Significant factors affect MMT adherence among illicit drug users including family income, history of drug rejections, concurrence in drug usage, far distance from MMT clinics, and having only peer. Patients in MMT private clinic had higher complete adherence than that of public MMT (OR = 1.82, 95% CI = 1.13; 2.94). Having contacts with peer drug users associated with a higher rate of incomplete adherence (OR = 2.83, 95% CI = 1.39; 5.73). Conclusions The findings support the establishment of private MMT clinics alongside public ones, while further researches to determine the optimal dose and ways to reduce the impact of peer drug user's influence are encouraged to be conducted.